Innovation, dual use and security [ managing the risks of emerging biological and chemical technologies - Tucker, Jonathan B. (MIT Press, 2012)
Recent advances in disciplines such as biotechnology, nanotechnology, and neuropharmacology entail a "dual-use dilemma" because they promise benefits for human health and welfare yet pose the risk of misuse for hostile purposes. The emerging field of synthetic genomics, for example, can produce custom DNA molecules for life-saving drugs but also makes possible the creation of deadly viral agents for biological warfare or terrorism. The challenge for policymakers is to prevent the misuse of these new technologies without forgoing their benefits . Innovation, Dual Use, and Security offers a systematic approach for managing the dual-use dilemma. The book presents a "decision framework" for assessing the security risks of emerging technologies and fashioning governance strategies to manage those risks. This framework is applied to fourteen contemporary case studies, including synthetic genomics, DNA shuffling and directed evolution, combinatorial chemistry, protein engineering, immunological modulation, and aerosol vaccines. The book also draws useful lessons from two historical cases: the development of the V-series nerve agents in Britain and the use and misuse of LSD by the U.S. Army and the CIA. Innovation, Dual Use, and Security offers a comprehensive, multifaceted introduction to the challenges of governing dual-use technologies in an era of rapid innovation. The book will be of interest to government officials and other practitioners as well as to students and scholars in security studies, science and technology studies, biology, and chemistry.